Differences in Clinical Presentation, Rate of Pulmonary Embolism, and Risk Factors Among Patients With Deep Vein Thrombosis in Unusual Sites. (5th September 2019) - Porfidia, Angelo; Porceddu, Enrica; Feliciani, Daniela; Giordano, Marzia; Agostini, Fabiana; Ciocci, Giulia; Cammà, Giulia; Giarretta, Igor; Gaetani, Eleonora; Tondi, Paolo; Pola, Roberto
Unusual site deep vein thrombosis (USDVT) is an uncommon form of venous thromboembolism with heterogeneous signs and symptoms, unknown rate of pulmonary embolism (PE), and poorly defined risk factors. We conducted a retrospective analysis of 107 consecutive cases of USDVTs, discharged from our University Hospital over a period of 2 years. Patients were classified based on the site of thrombosis and distinguished between patients with cerebral vein thrombosis, jugular vein thrombosis, thrombosis of the deep veins of the upper extremities, and abdominal vein thrombosis. We found statistically significant differences between groups in terms of age ( P < .0001) and gender distribution ( P < .05). We also found that the rate of symptomatic patients was significantly different between groups ( P < .0001). Another interesting finding was the significant difference between groups in terms of rate of PE ( P < .01). Finally, we found statistically significant differences between groups in terms of risk factors for thrombosis, in particular cancer ( P < .01). Unprovoked cases were differently distributed among groups ( P < .0001). This study highlights differences between patients with USDVT, which depend on the site of thrombosis, and provides data which might be useful in clinical practice.